PENGARUH PENGETAHUAN PRODUK, LABEL DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN KOSMETIK HALAL DENGAN HARGA SEBAGAI MEDIASI: Dibuat oleh Artantri Nugraheni, Sobrotul Imtikhanah dan Fadli Hudaya (Dosen dan Maahasiswa FEB Universitas Muhammadiyah Pekajangan Pekalongan) - Fadli Hudaya; Artantri Nugraheni; Sobrotul Imtikhanah (FEB Universitas Muhammadiyah Pekajangan Pekalongan, 2021)
This study aimed to analyze the effect of Product Knowledge, Halal Label and Promotion on Purchasing Decisions of Halal Cosmetics Products with Price as a Mediation variable. The object in this study was a student at the Faculty of Economics and Business, University of Muhammadiyah Pekajangan Pekalongan. The sampling technique used was purposive sampling technique with a sample of 100 respondents. Primary data was collected through questionnaires using a Likert scale. The analysis technique in this study used path analysis with the mediation test using the Sobel test. The results of this study indicated that: (1) Product Knowledge had a significant effect on Purchasing Decisions for Halal Cosmetics Products. (2) Halal Label had a significant effect on Purchasing Decisions for Halal Cosmetic Product. (3) Promotion had a significant effect on the Decisions to Purchase Halal Cosmetics Products. (4) Price can be a mediating variable between Product Knowledge, Halal Label and Promotion on Purchasing Decisions of Halal Cosmetics Products. Keywords: Product Knowledge, Halal Label, Promotion, Purchasing Decisions and Price.